Integration of Technology Readiness Index (TRI) Into the Technology Acceptance Model (TAM) for Explaining Behavior in Adoption of (Asian Education Studies, 2020)
Recently, Building Information Modelling (BIM) technology has attracted much attention in the Architecture, Engineering and Construction (AEC) industry and is becoming globally-recognized standards. The primary objective of this study is to gain better understanding of the drivers and barriers to the adoption of BIM. There is abundance of theories on technology adoption among which this study applies the Technology Acceptance Model (TAM) proposed by Davis (1989) to analyze the adoption and the use of the BIM technology by exploring implications of perceived ease of use, perceived usefulness, attitudes, behavioral intention and actual usage. In addition, this study integrates Technology Readiness Index (TRI) to explain adoption of BIM. With data collected through an online survey, findings of this study will assist in explaining behavior in adoption of BIM that may facilitate realizing the advantages of the BIM technology.